Speaking Problems Faced by Lower Secondary School Efl Learners: Masalah Berbicara yang Dihadapi oleh Peserta Didik Sekolah Menengah Pertama - Julfah, Julfah; Megawati, Fika (Universitas Muhammadiyah Sidoarjo, 2023)
Speaking is one of the important English learning skills to master. This study is about the analysis of students' difficulties in speaking English at SMP Muhammadiyah 10 Sidoarjo, which aims to find out the problems of speaking English experienced by students in grades 7A and 7B of SMP Muhammadiyah 10 Sidoarjo.In this study, researchers used qualitative research methods. By using the subject of classes 7A and 7B consisting of 44 students. In collecting data, researchers used questionnaires, interviews, and observations. Researchers used three main phases of data analysis: data reduction, data presentation, and drawing conclusions. From the data analysis, the researcher found the difficulties and factors experienced by students in learning to speak English at SMP Muhammadiyah 10 Sidoarjo, as follows: lack of vocabulary, lack of pronunciation, fear of making mistakes, and shame. Of these problems, the most dominant problems are vocabulary and pronunciation. Most of them stated that they were afraid to speak because of their lack of vocabulary and pronunciation. They feel afraid if they make mistakes in pronouncing words in English.